2015
DOI: 10.1007/s13277-015-4088-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CDC5L is associated with tumor progression in gliomas

Abstract: Cell division cycle 5-like (CDC5L) protein is a cell cycle regulator of the G2/M transition and has been reported to participate in the catalytic step of pre-messenger RNA (mRNA) splicing and DNA damage repair. Recently, it was also found to act as a candidate oncogene in osteosarcoma and cervical tumors. However, the role of CDC5L expression in tumor biology was still unclear. Here, we analyzed the expression and clinical significance of CDC5L in gliomas. The expression of CDC5L in fresh glioma tissues and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Moreover, meiotic resumption of immature oocytes in humans (4) and mice (58) could be hindered by DNA DSB damage, therefore the DNA DSB damage induced partially by the low CDC5L level may help explain the lower maturation rate as observed in BCB-negative oocytes. Third, depletion of CDC5L causes a mitotic catastrophe of HeLa cells through induction of apoptosis (39), and promotes apoptosis in human glioma cell lines (59). Thus the low CDC5L-induced apoptosis might be one reason for the higher death rate in BCB-negative oocytes.…”
Section: Cdc5l and Oocyte Maturationmentioning
confidence: 99%
“…Moreover, meiotic resumption of immature oocytes in humans (4) and mice (58) could be hindered by DNA DSB damage, therefore the DNA DSB damage induced partially by the low CDC5L level may help explain the lower maturation rate as observed in BCB-negative oocytes. Third, depletion of CDC5L causes a mitotic catastrophe of HeLa cells through induction of apoptosis (39), and promotes apoptosis in human glioma cell lines (59). Thus the low CDC5L-induced apoptosis might be one reason for the higher death rate in BCB-negative oocytes.…”
Section: Cdc5l and Oocyte Maturationmentioning
confidence: 99%
“…Cell division cycle 5-like (CDC5L) is a cell cycle regulatory element of G2/M transformation and is involved in the catalytic steps of mRNA splicing and DNA damage repair. Studies indicated that CDC5L expression in glioma and hepatocellular carcinoma was increased, and CDC5L interference could increase the cell cycle arrest in G2 phase and inhibit the proliferation of glioma cells and hepatoma cells [15,16]. However, CDC5L has not been studied in MM.…”
Section: Introductionmentioning
confidence: 99%
“…In the current gene signature list, CDC5L is correlated with advanced TNM stage of osteosarcoma ( 25 ) and responds poorly to neo-adjuvant chemotherapy ( 26 ). Overexpression of CDC5L favors cell cycle progression of hepatocellular carcinoma cells ( 27 ) and also plays an important role in glioma ( 28 ). TGFBR2 might be a key gene associated with sarcoma ( 29 ).…”
Section: Discussionmentioning
confidence: 99%